2018
DOI: 10.5465/amj.2016.0765
|View full text |Cite
|
Sign up to set email alerts
|

Are Family Firms Good Employers?

Abstract: Family firms employ about 60 percent of the global workforce. While it is widely assumed that they are good employers, data about their conduct is mixed. In this study, we extend stewardship and agency theories to test competing propositions about the impact of family on employment practices using data from 14,961 private Belgian firms over a 19-year period. Higher investments, lower dividend payout, and higher risk tolerance indicate that family firms are better financial stewards of their companies than nonf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 197 publications
(201 citation statements)
references
References 165 publications
(246 reference statements)
9
187
0
5
Order By: Relevance
“…This result is consistent with the postulation that firms training their employees tend to adopt other strategic human resources management practices too, such as monitoring employee relations with specific tools. Second, in line with Neckebrouck et al (), the first column in Tables and reveals a negative correlation between Family (%) ( β = −.076, p < .01), Family ( β = −3.076, p < .001), and Training & Development practices. Therefore, by multiplying these coefficients with the direct impact of Training & Development on Environment (i.e., second column, β = .944 and β = .946 in Tables and , respectively), we obtain the effect of family blockholders on Environment , which is mediated by Training & Development (coefficients of Family [%] and Family reported in the third column).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This result is consistent with the postulation that firms training their employees tend to adopt other strategic human resources management practices too, such as monitoring employee relations with specific tools. Second, in line with Neckebrouck et al (), the first column in Tables and reveals a negative correlation between Family (%) ( β = −.076, p < .01), Family ( β = −3.076, p < .001), and Training & Development practices. Therefore, by multiplying these coefficients with the direct impact of Training & Development on Environment (i.e., second column, β = .944 and β = .946 in Tables and , respectively), we obtain the effect of family blockholders on Environment , which is mediated by Training & Development (coefficients of Family [%] and Family reported in the third column).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, our study shows that listed family firms are penalized (at least in their environmental performance) for being family‐owned, which is in line with other studies that showed family firms have limited access to resources (Sirmon & Hitt, ); experience self‐selection of particular human resources, such as more conservative employees (Hauswald et al, ); exhibit bifurcation bias (Daspit et al, ); and implement poor employment practices (Neckebrouck et al, ). Overall, the studies seem to indicate that regardless of firm size, family firms fail to manage human resources (e.g., Kotey & Folker, ; Neckebrouck et al, ), and based on our empirical evidence, the negative features of family business persist even when they are under market disciplinary measures, such as being listed. However, although the dominant logic approach in family business studies assumes that family firms have different sets of goals to nonfamily firms (Aparicio et al, )—which creates specific social, emotional, and economic endowments (Gómez‐Mejía et al, ) linking family and business and affecting corporate governance (Carney, ) and managerial practices (Sirmon & Hitt, )—hardly any evidence exists of the mechanisms determining the underdevelopment of human resource practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations